2016
DOI: 10.12659/pjr.895190
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Metastasis From Carcinoma of the Gall Bladder: Need for Bone Scintigraphy Justified?

Abstract: SummaryBackgroundCarcinoma of the gall bladder has a guarded prognosis with predominant sites of involvement being liver and regional nodes. Osseous metastasis in carcinoma of the gall bladder is rare and hence bone scintigraphy does not form a part of the routine work-up for such patients.Case ReportsWe describe two patients with carcinoma of the gall bladder with osteolytic metastasis (stage 4). Conservative treatment was planned but both of them succumbed to the illness.ConclusionsWe thus highlight the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Onwuchekwa et al 12 reported skull metastasis and Humeres et al 13 reported multiple lytic bone metastasis in GBC cases. Similar cases are reported from India by Shivendra et al , Kumar et al 14, Jain et al 15, Ramachandran et al 16, Prakash et al 17, Joshi et al 18, Chaudhari et al 19, Puranik et al 20, Joel et al 21, Aswani and Hira22, Varshney et al 23 and Sinha et al 24 (table 1). 5 Incidentally, most of such reports are from India, with very scarce data from outside India.…”
Section: Discussionsupporting
confidence: 77%
“…Onwuchekwa et al 12 reported skull metastasis and Humeres et al 13 reported multiple lytic bone metastasis in GBC cases. Similar cases are reported from India by Shivendra et al , Kumar et al 14, Jain et al 15, Ramachandran et al 16, Prakash et al 17, Joshi et al 18, Chaudhari et al 19, Puranik et al 20, Joel et al 21, Aswani and Hira22, Varshney et al 23 and Sinha et al 24 (table 1). 5 Incidentally, most of such reports are from India, with very scarce data from outside India.…”
Section: Discussionsupporting
confidence: 77%
“…This distribution of metastasis was also seen in our study, with liver as the most common site of metastasis. Lung and bone metastasis is quite rare, and our series had just one each [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…As such, combinatorial treatment regimens incorporating chemotherapy, targeted therapies, and immunotherapies are actively being explored to extend survival and quality of life [8,9]. Despite several reported cases and series in the literature, population-level data on treatment outcomes and prognostic evaluation of GBC remains limited, punctuated by anecdotal experiences [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, beyond the already established poor prognosis of GBC, the presence of isolated bone metastasis in GBC is associated with an even more unfavorable outcome when compared to isolated lung and distant lymph node metastasis [16]. However, there is a paucity of literature exploring bone metastasis in gallbladder cancers, with the majority of the existing data being derived from case reports and small series [6,10,11]. To address this research gap, we used the Surveillance, Epidemiology, and End Results (SEER) database, a large cancer registry, to conduct a comprehensive analysis of bone metastasis in patients with gallbladder adenocarcinoma, the most common histologic subtype of the gallbladder cancers [15].…”
Section: Introductionmentioning
confidence: 99%